2007
DOI: 10.1007/s11064-007-9432-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Dicholesteroyl Diselenide and Diphenyl Diselenide as Antioxidant Agents and their Effect on the Activities of Na+/K+ ATPase and δ-Aminolevulinic acid Dehydratase in the Rat Brain

Abstract: The present study sought to evaluate the effect of a newly synthesized selenium compound, dicholesteroyl diselenide (DCDS) and diphenyl diselenide (DPDS) on the activities of delta-aminolevulinate dehydratase and Na+/K+-ATPase in the rat brain. The glutathione peroxidase mimetic activity of the two compounds as well as their ability to oxidize mono- and di- thiols were also evaluated. The antioxidant effects were tested by measuring the ability of the compounds to inhibit the formation of thiobarbituric acid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…We have observed that intraperitoneal administration of DPDS dissolved in DMSO can cause convulsion in mice (Brito et al 2006). Recent reports from our group also show that DPDS inhibits cerebral ALA-D and Na + /K + -ATPase in vitro (Kade et al 2008), and that DPDS causes seizures, with attendant increases in oxidative stress parameters in the brains of rat pups, further indicating the possible mechanism of its neurotoxicity (Prigol et al 2007). Such additional effects notwithstanding, the present study demonstrated that the treatment of diabetic rats with oral administration of DPDS in soya bean oil at 3 mg/kg exerted a considerable hypoglycemic effect.…”
Section: Discussionmentioning
confidence: 71%
“…We have observed that intraperitoneal administration of DPDS dissolved in DMSO can cause convulsion in mice (Brito et al 2006). Recent reports from our group also show that DPDS inhibits cerebral ALA-D and Na + /K + -ATPase in vitro (Kade et al 2008), and that DPDS causes seizures, with attendant increases in oxidative stress parameters in the brains of rat pups, further indicating the possible mechanism of its neurotoxicity (Prigol et al 2007). Such additional effects notwithstanding, the present study demonstrated that the treatment of diabetic rats with oral administration of DPDS in soya bean oil at 3 mg/kg exerted a considerable hypoglycemic effect.…”
Section: Discussionmentioning
confidence: 71%
“…Several proteins have been shown to be inactivated by selenols. In mammals, they include important regulatory proteins such as the NF-B transcription factor (53), signal transduction kinases such as c-Jun N-terminal kinase (54) and protein kinase C (55), and Na ϩ /K ϩ -ATPases (56). In yeast, ebselen, a synthetic organoselenium compound converted into a selenol in vivo, was shown to inhibit the activity of the plasma membrane H ϩ -ATPase (Pma1p), involved in the regulation of intracellular pH and essential for growth (57).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,13 Indeed, the interaction of diphenyl diselenide with insect, fish and mammalian δ-ALA-D and other thiolcontaining enzymes or proteins, such as Na + ,K + -ATPase and vicinal mitochondrial thiol containing proteins, can be facilitated by the proximity or by the presence of vicinal thiol groups in their tertiary structure (Figure 4). [13][14][15] Taken together, these in vitro results can indicate that high molecular weight containing-molecules, i.e., specific classes of proteins or enzymes can be preferential targets of diphenyl diselenide and analogs than GSH.…”
Section: Molecular Toxicology Of Diphenyl Diselenidementioning
confidence: 99%